POTRET MASYARAKAT MISKIN PENYANDANG DISABILITAS DI PONOROGO : PENYEBAB DAN SOLUSI KEBIJAKAN PEMERINTAH - Intan Pradana; B Widiyahseno (Jurnal Ilmu Pemerintahan Suara Khatulistiwa, 2022)
Abstract This research begins with a phenomenon that occurs in people with disabilities. As a result, organ function is not perfect. This limitation does not provide freedom for persons with disabilities to carry out daily activities. Therefore, people with disabilities need special attention in developing their independence so that they can carry out their social functions. The purpose of this study is to clarify the role of local governments in alleviating poverty problems for groups of people with disabilities. This research was conducted using a descriptive approach with a qualitative approach. The investigation comes from the description of the informants conducted through interviews, not numbers. Collecting data for this research through observation, interviews, and literature study. Data analysis for this study involves collecting all the data and reducing the data to draw conclusions as a result of the study. The results of the study show that the government is making efforts to empower people with disabilities which is supported by socialization and training, especially for people with disabilities. Keyword : Poverty, Persons with disabilities, Government Policy